Online Experimental Auctions - Anouar El Haji; Jayson L. Lusk; Ayse Mermer; Sander Onderstal (Tinbergen Institute, 2023)
For companies, it is essential to obtain information about customers' preferences to successfully market their products and services. Experimental auctions are a promising method for acquiring such information considering that they are incentive compatible and non-hypothetical. Their applicability to solving real-world problems has been limited by the need to conduct these with a representative sample. While most research on experimental auctions relies on laboratory experiments with students as participants, more recently, experimental auctions in the field have become increasingly important. In this paper, we explore a novel way of conducting experimental auctions in the field using online communities of potential consumers. We discuss design challenges and present marketing applications.
Keywords: 330; Experimental auctions; Field experiments; Market research; Value elicitation